Bone and joint infections in infants under three months of age. (9th October 2018) - Mediamolle, Nicolas; Mallet, Cindy; Aupiais, Camille; Doit, Catherine; Ntika, Serge; Vialle, Raphael; Grimprel, Emmanuel; Pejin, Zagorka; Bonacorsi, Stephane; Lorrot, Mathie
Abstract: Aim: Studies on bone and joint infections (BJI) in infants under three months are rare. We described the clinical and paraclinical features and outcomes of infants hospitalised with BJI under three months of age. Methods: The French National Hospital Discharge Database provided data on BJIs in infants under three months of age from January 2004 to 2015 in three Parisian Paediatric teaching hospitals. Results: We included 71 infants under three months of age with BJI, the median age was 25 days, and the interquartile range (IQR) was 17–43 days. The most common infection sites were the hip (32%) and knee (32%). Symptoms included pain (94%), limited mobility (87%) and/or fever (52%). There were 11 (15.5%) cases of nosocomial BJI. A pathogen was identified in 51 infants (71.8%), including Streptococcus agalactiae (45%), Staphylococcus aureus (22%) and Escherichia coli (18%). The initial median C‐reactive protein test rate was 31 mg/L (IQR 17–68). Of the 34 infants followed for more than one year, four developed severe orthopaedic conditions such as epiphysiodesis, limb length discrepancy, bone necrosis and/or impaired limb function. Conclusion: Streptococcus agalactiae was the most common cause of BJI in infants under three months. Orthopaedic sequelae were rare, but severe, and required long‐term follow‐up.